The evolution of thecideide microstructures and textures: traced from Triassic to Holocene. (2nd April 2021) - Simonet Roda, Maria; Griesshaber, Erika; Angiolini, Lucia; Harper, David A.T.; Jansen, Ulrich; Bitner, Maria Aleksandra; Henkel, Daniela; Manzanero, Eloy; Müller, Tamás; Tomašových, Adam; Eisenhauer, Anton; Ziegler, Andreas; et al.
Abstract : Thecideide brachiopods are an anomalous group of invertebrates. In this study, we discuss the evolution of thecideide brachiopods from the Triassic to the Holocene and base our results and conclusions on microstructure and texture measurements gained from electron backscatter diffraction (EBSD). In fossil and Recent thecideide shells, we observe the following mineral units: (1) nanometric to small granules; (2) acicles; (3) fibres; (4) polygonal crystals; and (5) large roundish crystals. We trace for thecideide shells the change of mineral unit characteristics such as morphology, size, orientation, arrangement and distribution pattern. Triassic thecideide shells contain extensive sections formed of fibres interspersed with large, roundish crystals. Upper Cretaceous to Pleistocene thecideide hard tissues consist of a matrix of minute to small grains reinforced by acicles and small polygonal crystals. Recent thecideide species form their shell of mineral units that show a wide range of shapes, sizes and arrangements. We find from Late Triassic to Recent a gradual decrease in mineral unit size, regularity of mineral unit morphology and orientation and the degree of calcite co‐orientation. While crystallite co‐orientation is the highest for fibrous microstructures, it is strikingly low for taxa that form their shell out of nanogranular to acicular mineral units. Our results indicate that Upper Jurassic species represent transitional forms between ancient taxa with fibrous shells and Recent forms that construct their shells of acicles and granules. We attribute the observed changes in microstructure and texture to be an adaptation to a different habitat and lifestyle associated with cementation to hard substrates.